Sutureless aortic valve replacement - Di Eusanio, Marco; Phan, Kevin (Annals of Cardiothoracic Surgery, 2015)
The increasing incidence of aortic stenosis and greater morbidities and risk profiles on the contemporary patient population has driven the development of minimally invasive aortic valve surgery and percutaneous transcatheter aortic valve implantation (TAVI) techniques to reduce surgical trauma. Recent technological developments have led to an alternative minimally invasive option which avoids the placement and tying of sutures, known as “sutureless” or rapid deployment aortic valves. Potential advantages for sutureless aortic prostheses include reducing cross-clamp and cardiopulmonary bypass (CPB) duration, facilitating minimally invasive surgery and complex cardiac interventions, whilst maintaining satisfactory hemodynamic outcomes and low paravalvular leak rates. However, given its recent developments, the majority of evidence regarding sutureless aortic valve replacement (SU-AVR) is limited to observational studies and there is a paucity of adequately-powered randomized studies. Recently, the International Valvular Surgery Study Group (IVSSG) has formulated to conduct the Sutureless Projects, set to be the largest international collaborative group to investigate this technology. This keynote lecture will overview the use, the potential advantages, the caveats, and current evidence of sutureless and rapid deployment aortic valve replacement (AVR).